Measuring Self‐Association of Pt Complexes by 195Pt NMR. Issue 11 (19th April 2017) - Suleymanova, Alfiya F.; Eltsov, Oleg S.; Kozhevnikov, Dmitry N.; Lantushenko, Anastasia O.; Evstigneev, Maxim P.; Kozhevnikov, Valery N.
Abstract: A highly soluble neutral cyclometallated Pt complex of C N N type was prepared and its self‐aggregation in CDCl3 solution was studied by NMR dilution method. It was shown that 195 Pt NMR can be used to quantify aggregation and therefore be potentially applied to many other Pt complexes. Two‐dimensional HMBC 1 H‐ 195 Pt technique increases sensitivity of experiment and allowed recording 195 Pt chemical shift values at concentration as low as 1 mM and it was observed that opposite to shielding of aromatic protons, Pt nucleus is deshielded upon increase of concentration. Abstract : 195 Pt NMR was successfully used to quantify self‐aggregation of neutral cyclometallated Pt(II) complexes in non‐polar solvent. The method is not dependent on the ligand and can potentially be applied to any Pt(II) complexes.